The upper limb of Homo naledi. Issue 104 (March 2017) - Feuerriegel, Elen M.; Green, David J.; Walker, Christopher S.; Schmid, Peter; Hawks, John; Berger, Lee R.; Churchill, Steven E.
Abstract: The evolutionary transition from an ape-like to human-like upper extremity occurred in the context of a behavioral shift from an upper limb predominantly involved in locomotion to one adapted for manipulation. Selection for overarm throwing and endurance running is thought to have further shaped modern human shoulder girdle morphology and its position about the thorax. Homo naledi (Dinaledi Chamber, Rising Star Cave, Cradle of Humankind, South Africa) combines an australopith-like cranial capacity with dental characteristics akin to early Homo . Although the hand, foot, and lower limb display many derived morphologies, the upper limb retains many primitive traits. Here, we describe the H. naledi upper extremity (excluding the hand) in detail and in a comparative context to evaluate the diversity of clavicular, scapular, humeral, radial, and ulnar morphology among early hominins and later Homo . Homo naledi had a scapula with a markedly cranially-oriented glenoid, a humerus with extremely low torsion, and an australopith-like clavicle. These traits indicate that the H. naledi scapula was situated superiorly and laterally on the thorax. This shoulder girdle configuration is more similar to that of Australopithecus and distinct from that of modern humans, whose scapulae are positioned low and dorsally about the thorax. Although early Homo erectus maintains many primitive clavicular and humeral features, its derived scapular morphology suggests a loss of climbing adaptations. In contrast, the H. naledi upper limb is markedly primitive, retaining morphology conducive to climbing while lacking many of the derived features related to effective throwing or running purported to characterize other members of early Homo .